Pd(II)-Catalyzed Directing-Group-Aided C–H Arylation and Alkylation of Pyrene Core: Synthesis of C1,C2- and C1,C10-Disubstituted Pyrene Motifs - Dalal, Arup; Babu, Srinivasarao Arulananda (Synthesis, 2021)
We report the application of the Pd(II)-catalyzed, directing-group-aided C–H arylation/alkylation tactics to functionalize the pyrene core, especially, the relatively inaccessible C2 and K-region C10 positions of the pyrene core and augmentation of the library of pyrene derivatives with C1,C2- and C1,C10-disubstituted pyrene motifs. The Pd(II)-catalyzed β-C–H arylation/alkylation of the C2-position of pyrene-1-carboxamide possessing an 8-aminoquinoline directing group yielded various C1,C2-disubstituted pyrenes. Similarly, the Pd(II)-catalyzed selective γ-C–H arylation/alkylation of the C10-position of N-(pyren-1-yl)picolinamide, possessing a picolinamide directing group, yielded various C1,C10-disubstituted pyrenes. Examples of C(9)–H arylation of pyrene-1-carboxamide and the removal of the directing group after the C–H arylation/alkylation reactions were also shown. The structures of representative pyrene derivatives were confirmed by the X-ray structure analysis. Given the importance of the pyrene derivatives in various fields of chemical sciences, this report is a contribution towards augmentation of the library of pyrene derivatives with C1,C2- and C1,C10-disubstituted pyrene amide motifs.
Keywords: C–H activation; C–H arylation/alkylation; C–H functionalization; bidentate directing group; carboxamides; palladium; pyrene